Structure of γ‐conglutin: insight into the quaternary structure of 7S basic globulins from legumes. (1st February 2015) - Czubinski, Jaroslaw; Barciszewski, Jakub; Gilski, Miroslaw; Szpotkowski, Kamil; Debski, Janusz; Lampart‐Szczapa, Eleonora; Jaskolski, Mariusz
<x xml:space="preserve">Abstract</x> γ‐Conglutin from lupin seeds is an unusual 7S basic globulin protein. It is capable of reducing glycaemia in mammals, but the structural basis of this activity is not known. γ‐Conglutin shares a high level of structural homology with glycoside hydrolase inhibitor proteins, although it lacks any kind of inhibitory activity against plant cell‐wall degradation enzymes. In addition, γ‐conglutin displays a less pronounced structural similarity to pepsin‐like aspartic proteases, but it is proteolytically dysfunctional. Only one structural study of a legume 7S basic globulin, that isolated from soybean, has been reported to date. The quaternary assembly of soybean 7S basic globulin (Bg7S) is arranged as a cruciform‐shaped tetramer comprised of two superposed dimers. Here, the crystal structure of γ‐conglutin isolated from Lupinus angustifolius seeds (LangC) is presented. The polypeptide chain of LangC is post‐translationally cleaved into α and β subunits but retains its covalent integrity owing to a disulfide bridge. The protomers of LangC undergo an intricate quaternary assembly, resulting in a ring‐like hexamer with noncrystallographic D3 symmetry. The twofold‐related dimers are similar to those in Bg7S but their assembly is different as a consequence of mutations in a β‐strand that is involved in intermolecular β‐sheet formation in γ‐conglutin. Structural elucidation of γ‐conglutin will help to explain its physiological role, especially in the evolutionary context, and will guide further research into the hypoglycaemic activity of this protein in humans, with potential consequences for novel antidiabetic therapies.